Sosialisasi Pengembangan Usaha Mikro Kecil Menengah di Desa Posso dan Desa Bubode Kabupaten Gorontalo Utara - Hanasi, Raihan A.; Kadir, Muhamad Khairun K.; Malae, Andris K.; Kasim, Mamang; Suleman, Delvi; Pulogu, Siska Irhamnawati; Bumulo, Sahrain (Sosiologi Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This activity is carried out as part of a community service program with the primary focus on providing socialization related to the development strategies of micro, small, and medium enterprises (MSMEs) in Posso Village and Bubode Village. The research aims to provide understanding to the community, especially those involved in MSME groups, about the importance of a strategy in MSME development, particularly strategies related to Strengthening Access to Capital, Marketing and Branding, and Improving Product Quality. The target of this activity is the MSME groups in the two villages, namely Bubode Village and Posso Village. The socialization activities span over 3 days, starting with gathering information related to the challenges faced by MSME groups in both villages, followed by designing effective development strategies applicable to these groups. Through a participatory approach, the activity involves various stakeholders from both villages to create sustainable solutions collaboratively. The expected outcome of this activity is to make a positive contribution to local economic development and community welfare, as well as to enhance practical understanding and implementation of strategies that can improve the competitiveness of MSMEs in both villages